Realization of the right to a fair trial: separate legislative novels - Рябченко, Олена Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article presents a critical analysis of the Law of Ukraine On Judicial System And Status Of Judges in the new edition. It is stated that the revision of the mentioned law actually took place not only with the adoption of its new edition, but with the expansion of the Supreme Court of Ukraine jurisdiction in condition of the existence of Constitutional Court of Ukraine another legal position stated in a Decision № 8-RP/2010 dated 11th of March, 2010. In this regard, it is specified that the establishment of the Supreme Court of Ukraine legal status as the highest in the system of general courts with case review jurisdiction identifies the need for further analysis. It is highlighted as a positive the definition of the grounds for disciplinary proceedings against judge, as well as differentiation of disciplinary sanctions. The emphasis on the need to solve highlighted and other problematic issues, including at the doctrinal level, is put. Along with this, the following provisions, that relate to: disciplinary sanction repayment terms, the determining criterion of which is obscure; the status of the subject of checking grounds for subjecting a judge to disciplinary liability cause certain cautions. It is also mentioned about the possibility of problems arising when disciplinary responsibility is applied to judges, starting with the violations legal qualification implementation and completing the establishing of the prescription terms for subjecting to disciplinary responsibility.